Одержання адгезійної добавки з рідких продуктів коксування вугілля і модифікування нею дорожніх бітумів - Гурі , Ісайя Борбеїйонг (Національний університет «Львівська політехніка», 2022)
В дисертаційному дослідженні вирішено важливе науково-технічне завдання: одержано ефективну адгезійну добавку до дорожніх нафтових бітумів з рідких продуктів коксування вугілля (кумарон-інденової фракції (КІФ)). Проаналізовано досвід вітчизняних і світових науковців та представників промисловості в застосуванні і розробленні нових різноманітних модифікаторів дорожніх бітумів. На основі огляду наукової та патентної літератури запропоновано напрямок проведення досліджень. Опрацьовано сучасні й існуючі стандартні методики досліджень бітумів, їх модифікаторів та адгезійних додатків, асфальтобетонних сумішей. Визначено основні показники і склад сировини: широкої та вузької кумарон-інденових фракцій, які одержані на ПАТ «ЮЖКОКС» (м. Кам’янське, Україна); двох зразків бітумів марок БНД 70/100, відібраних на ПАТ «Укртатнафта» (м.Кремечук, Україна); щебеню гранітного (фр. 5-20 мм, фр. 20-40 мм), відібраного на ТОВ «Мокрянський кам’яний кар’єр №3» (м. Запоріжжя, Україна). The dissertation study solved an essential scientific and technical task under the theme: an effective adhesive additive to road petroleum bitumen from liquid products of coal coking (coumarone-indene fraction (CIF)). The experience of domestic and international scientists and industry representatives in the application and development of new and various road bitumen modifiers was analyzed. Based on the review of scientific and patent literature, the direction of research is proposed. Modern and existing standard methods of research of bitumen, their modifiers, and adhesive applications, asphalt concrete mixtures have been developed. The main parameters and composition of the raw materials: wide and narrow coumaroneindene fractions, were obtained at PJSC «YUZHKOKS» (Kamyanske, Ukraine); two samples of BND 70/100 bitumen were selected at PJSC «Ukrtatnafta» ( Kremenchuk, Ukraine) and granite crushed stone (fr. 5-20 mm, fr. 20-40 mm), selected at «Mokryansky stone quarry No. 3» LLC (Zaporizhia, Ukraine) were determined. The goal of this work is achieved by co-oligomeric carbocation of a narrow CIF (boiling point of 140-190 °C) in the presence of carbazole and TiCl4 as a catalyst to obtain coumarone-indene-carbazole resin (CICR), which, when added to road petroleum bitumen, significantly improves their adhesive properties.
Obtaining an adhesive promoter from liquid products of coal coking and bitumen modifying by it
Keywords: продукти коксування вугілля, інден, кумарон, карбазол, адгезійна добавка, дрожній бітум, модифікування, coal coking products, indene, coumarone, carbazole, adhesive additive, road bitumen, modification.; 665.775+665.775.4+665.044.7 (043.5)